2013
DOI: 10.1016/j.febslet.2013.05.035
|View full text |Cite
|
Sign up to set email alerts
|

LARP1 specifically recognizes the 3′ terminus of poly(A) mRNA

Abstract: Edited by Michael IbbaKeywords: RNA-directed immunoprecipitation Proteomics LAPP1 Poly(A) tail 5 0 TOP mRNA a b s t r a c t A poly(A) tail functions in mRNA turnover and in facilitating translation as a ribonucleoprotein complex with poly(A) binding proteins (PABPs). However, factors that associate with the poly(A) tail other than PABPs have not been described. Using proteomics, we identified candidate proteins that interact to the 3 0 terminus of the poly(A) tail. Among these proteins, we focused on La motif-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(151 citation statements)
references
References 25 publications
13
138
0
Order By: Relevance
“…5B). These results confirm the previously reported stimulatory effect of these LARPs on gene expression (Burrows et al 2010;Schäffler et al 2010;Yang et al 2011;Aoki et al 2013;Mura et al 2014;Tcherkezian et al 2014). The simultaneous knockdown of LARP4 and LARP4B led to a decrease in the luciferase activity by 55%.…”
Section: Larp4b Larp4 and Larp1 Interact With An Overlapping Set Ofsupporting
confidence: 91%
See 3 more Smart Citations
“…5B). These results confirm the previously reported stimulatory effect of these LARPs on gene expression (Burrows et al 2010;Schäffler et al 2010;Yang et al 2011;Aoki et al 2013;Mura et al 2014;Tcherkezian et al 2014). The simultaneous knockdown of LARP4 and LARP4B led to a decrease in the luciferase activity by 55%.…”
Section: Larp4b Larp4 and Larp1 Interact With An Overlapping Set Ofsupporting
confidence: 91%
“…Similar biochemical and functional properties were reported for LARP4B, LARP4, and LARP1. They are cytoplasmic proteins that translocate into stress granules under cellular stress conditions, interact with PABPC1, associate with actively translating ribosomes and exert stabilizing effects on target mRNAs (Burrows et al 2010;Schäffler et al 2010;Yang et al 2011;Aoki et al 2013;Mura et al 2014;Tcherkezian et al 2014). This suggests that they might fulfill overlapping or redundant functions in mRNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…72 This protein was previously shown to associate with and promote the stability of TOP mRNAs, 73 suggesting that LARP1 may regulate TOP mRNAs at different levels to control their expression in cells. Interestingly, 2 studies aiming to characterize the mTOR phosphoproteome repertoire have identified LARP1 as a potential mTORC1 phosphorylation substrate.…”
Section: Translational Control Of Top Mrnasmentioning
confidence: 99%